Asymmetric effects of monetary policy shocks across US states. Issue 5 (31st July 2019) - Furceri, Davide; Mazzola, Fabio; Pizzuto, Pietro
Abstract: This paper provides new empirical evidence of the asymmetric effects of monetary policy shocks across regions. Using a measure of unanticipated changes in the Fed's policy rates over the period 1969Q3–2008Q4 and a local projection method extended to account for spatial effects, we find that monetary policy tightening leads to a long‐lasting decrease in states' real personal income, with asymmetric effects across states that are amplified by spatial spillovers. The paper then investigates the role played by several transmission channels finding larger contractionary effects of monetary policy tightening in states with higher manufacturing share, smaller firms, smaller banks and higher house prices. Resumen: Este artículo aporta nuevas pruebas empíricas de los efectos asimétricos de las perturbaciones de la política monetaria en las distintas regiones. Mediante el uso de una medida de los cambios no previstos en las tasas de interés de la Reserva Federal durante el período del 3 er trimestre de 1969 al 4 o trimestre de 2008 y un método de proyección local ampliado para tener en cuenta los efectos espaciales, se encontró que el endurecimiento de la política monetaria conduce a una disminución duradera de los ingresos personales reales de los estados, con efectos asimétricos entre estados que se ven amplificados por spillovers espaciales. A continuación, se investiga el papel desempeñado por varios canales de transmisión y se observan efectos contractivos del endurecimiento de la política monetaria que son más grandes en los estados con mayor participación de las manufacturas, las empresas más pequeñas, los bancos más pequeños y los precios de la vivienda más elevados. 抄録: 本稿では、金融政策ショックが地域間で非対称的に作用していることを示す新たな実証分析を行う。1969年の第3四半期〜2008年の第4四半期における連邦準備制度理事会の政策金利の予想外の変化の測定と、空間的影響を考慮に入れて拡張したローカル予測手法を用いて、金融引き締めが、米国の個人実質所得の長期的な減少につながり、さらに空間的波及効果によって非対称的影響が米国全体で増幅されることが分かった。続いて、いくつかの波及経路の役割を調査したところ、製造業のシェアが大きく、企業および銀行の規模が小さく、住宅価格が高い州では、金融引き締めがもたらす緊縮効果がより大きいことが分かった。